تحليل التداخل النصي وتحول المعنى في ترجمة القصيدة SEBUAH JAKET BERLUMUR DARAH من اللغة الإندونيسية إلى العربية - Riska Amanda Putri; Lalu Turjiman Ahmad; Ahmad Habibi Syahid (UNiversitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study examines the translation of the poem “A jacket covered in blood by Taufik Ismail from Indonesian to Arabic by Nabilah Lubis, with the aim of analyzing intertextuality and meaning transformation in the translation of the poem. The research method used is descriptive qualitative. The research shows that the translation of this poem gives rise to cultural and political intertextuality between the two languages involved, as well as successfully maintaining the messages and nuances contained in the original text. Meaning transformation occurs in the translation process, where words or phrases in the original text are interpredted with different words in the target language to express similar or related meanings. This study provides a deeper understanding of the dynamics of poetry translation and the importance of considering linguistic, curtural, political and literary aspects the process